MvaT binds to the PexsC promoter to repress the type III secretion system in Pseudomonas aeruginosa - Yin, Liwen; Liu, Qi; Pan, Xiaolei; Lv, Chenjing; Bai, Yuxi; Bai, Fang; Cheng, Zhihui; Wu, Weihui; Ha, Un-Hwan; Jin, Yongxin (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa is an opportunistic human pathogen capable of causing a variety of acute and chronic infections. Its type III secretion system (T3SS) plays a critical role in pathogenesis during acute infection. ExsA is a master regulator that activates the expression of all T3SS genes. Transcription of exsA is driven by two distinct promoters, its own promoter PexsA and its operon promoter PexsC. Here, in combination with a DNA pull-down assay and mass spectrometric analysis, we found that a histone-like nucleoid-structuring (H-NS) family protein MvaT can bind to the PexsC promoter. Using EMSA and reporter assays, we further found that MvaT directly binds to the PexsC promoter to repress the expression of T3SS genes. The repression of MvaT on PexsC is independent of ExsA, with MvaT binding to the -429 to -380 bp region relative to the transcription start site of the exsC gene. The presented work further reveals the complex regulatory network of the T3SS in P. aeruginosa.